Extensions of the Cayley-Hamilton theorem for 2-D continuous-discrete linear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The Cayley-Hamilton theorem is extended for new classes of 2-D continuous-discrete linear systems.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka